High selectivity framework polymer membranes chemically tuned towards fast anion conduction - Junkai Fang; Guozhen Zhang; Marc-Antoni Goulet; Peipei Zuo; Yu Zhou; Hui Li; Jun Jiang; Michael D. Guiver; Zhengjin Yang; Tongwen Xu (Nature Communications)
Abstract Studying ion transport in the interaction confinement regime has important implications for membrane design and advanced electrochemical devices. A key example is the rapid-charging capability of aqueous organic redox flow batteries, enabled by near-frictionless Na+/K+ transport within triazine framework membranes. However, achieving similar breakthroughs for devices using anions (e.g., Cl-) is challenging due to the suppression of anion transport under confinement, known as the charge asymmetry effect. We present a series of anion-selective covalent triazine framework membranes with comparable densities of subnanometer ion transport channels and identical micropore size distributions, which help to overcome the charge asymmetry effect and promote fast anion conduction. We demonstrate that regulating the charge distribution in the membrane frameworks reduces the energy barrier for anion transport, resulting in nearly doubled Cl- conductivity and adding almost no additional energy barrier for F- transport. This membrane enables an aqueous organic redox flow battery using Cl- ions to operate at high current densities, exceeding battery performance demonstrated by current membranes. These findings could benefit various electrochemical devices and inspire single-species selectivity in separation membranes.